1994
DOI: 10.1111/j.1600-0714.1994.tb00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral melanocytic lesions: differences in expression of HMB‐45 and S‐100 antigens in round and spindle cells of malignant and benign lesions

Abstract: Immunohistochemistry and melanin bleaching were used to assess the expression of antigens identified by anti-S-100 and anti-HMB-45 antibodies on melanomas and intramucosal and blue nevi from the oral mucosa of 18 patients. Both antibodies reacted with cells in all three types of lesions, but there were differences in the expression of these antigens between the round and spindle cells within the lesions. In melanomas composed of round cells, the intensity and distribution of staining with HMB-45 was greater th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Our findings are in accordance with other authors who also found negative S-100 protein staining of blue nevi of the skin [22, 23], but in contrast to the results of Lovas et al [22] who found a positive S-100 staining in all of 5 examined intraoral blue nevi. Also Gazit and Daniels [24] found in all of 6 examined blue nevi of the oral mucosa a positive S-100 protein staining of the elongated spindle-shaped cells. HMB-45 is a monoclonal antibody that recognizes a premelanosomal glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in accordance with other authors who also found negative S-100 protein staining of blue nevi of the skin [22, 23], but in contrast to the results of Lovas et al [22] who found a positive S-100 staining in all of 5 examined intraoral blue nevi. Also Gazit and Daniels [24] found in all of 6 examined blue nevi of the oral mucosa a positive S-100 protein staining of the elongated spindle-shaped cells. HMB-45 is a monoclonal antibody that recognizes a premelanosomal glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Protein S-100, besides helping in determining tumor thickness, has been shown in some studies to be of a potential prognostic value, i.e. the intensity of staining by protein S-100 was in reverse correlation with the survival time [31][32][33] . All these routinely and most frequently used antibodies in the histopathologic diagnosis of OM are used in cases of melanocytic diff erentiation of tumor cells, i.e.…”
Section: Methods In the Diagnosis Of Melanomasmentioning
confidence: 99%
“…Anti-S-100, anti-HMB-45 and anti-Melan-A are the three most commonly used antibodies for the immunohistochemical diagnosis of primary oral MM. Previous studies have recorded a positive rate of 100% for anti-S-100 (3,7,11) and ~79% (range, 71-100%) for anti-HMB-45 (1,3,7,11). These results indicated that S-100 is a more sensitive marker than HMB-45 and Melan-A for immunohistochemically diagnosing MM.…”
Section: Discussionmentioning
confidence: 99%
“…MMs are known to have a high potential for malignancy, invasiveness and metastasis (1,2). Although MMs with characteristic melanin-pigmented tumor cells are easy to diagnose, amelanotic MMs (AMMs) are extremely difficult to diagnosis due to the absence of these cells (3,4). AMM can be divided into the following five types based on the varied clinical features observed: The pigmented nodular type, the non-pigmented nodular type, the pigmented macular type, the pigmented mixed type and the non-pigmented mixed type (5,6).…”
Section: Introductionmentioning
confidence: 99%